The Influence of Brand Credibility, Technological Innovation, and User Engagement on the Effectiveness of AI and Its Impact on the Reader Loyalty of Liputan6.com Digital Media Platform Readers - Dinda Virgia Yurendira; Dr. Osly Usman, M.Bus; Meta Bara Berutu, S.E., M.M (Journal of Digital Business and Global Economy, 2025)
This study analyzes the influence of brand credibility, technological innovation, and user engagement on reader loyalty, with AI effectiveness as a mediating variable in the context of AI presenters on digital media. Using a quantitative approach with PLS-SEM via SmartPLS, data were collected from 275 Liputan6.com readers aged 17-65 who had engaged with AI-presented news at least three times. The findings reveal that brand credibility, technological innovation, and user engagement positively affect both AI effectiveness and reader loyalty. AI effectiveness also significantly mediates the relationship between brand credibility and user engagement with reader loyalty, but not between technological innovation and reader loyalty. These results highlight the importance of trust and engagement in enhancing AI effectiveness to foster loyalty, while innovation must offer clear benefits to be impactful.